German FinTech Companies: A Market Overview and Volume Estimates - Gregor Dorfleitner; Julia Kreppmeier; Ralf Laschinger (Credit and Capital Markets – Kredit und Kapital, 2023)
The FinTech market in Germany is a dynamic and growing field that is difficult to observe in its entirety. This report provides a hand-collected market overview of the FinTech market in Germany, as well as an application case in terms of volume estimates for the financing and asset management segments through December 2021. The data includes various verified characteristics of 978 unique companies that can be classified under the financial technology sector and operate in Germany. Each observation represents a company with 24 variables, including name, address, legal form, founders with corresponding LinkedIn accounts, registration number or company ID, assignment to FinTech segments and sub-segments, banking cooperation, URL address, local court, former name, operating status. We provide the description of the variables as well as a taxonomy to categorize FinTechs. The dataset contains both established companies and startups and presents valuable information for researchers, practitioners and also regulators.
Keywords: G10; G20; G28; K20; L81; M13; 330; FinTech; Germany; Start-Up; Financial Technology; Digital Finance; Entrepreneurship; Supervision